Progress in Tribological Properties of Nano-Composite Hard Coatings under Water Lubrication - Qianzhi Wang; Fei Zhou (Lubricants, 2017)
The tribological properties, under water-lubricated conditions, of three major nano-composite coatings, i.e., diamond-like carbon (DLC or a-C), amorphous carbon nitride (a-CNx) and transition metallic nitride-based (TiN-based, CrN-based), coatings are reviewed. The influences of microstructure (composition and architecture) and test conditions (counterparts and friction parameters) on their friction and wear behavior under water lubrication are systematically elucidated. In general, DLC and a-CNx coatings exhibit superior tribological performance under water lubrication due to the formation of the hydrophilic group and the lubricating layer with low shear strength, respectively. In contrast, TiN-based and CrN-based coatings present relatively poor tribological performance in pure water, but are expected to present promising applications in sea water because of their good corrosion resistance. No matter what kind of coatings, an appropriate selection of counterpart materials would make their water-lubricated tribological properties more prominent. Currently, Si-based materials are deemed as beneficial counterparts under water lubrication due to the formation of silica gel originating from the hydration of Si. In the meantime, the tribological properties of nano-composite coatings in water could be enhanced at appropriate normal load and sliding velocity due to mixed or hydrodynamic lubrication. At the end of this article, the main research that is now being developed concerning the development of nano-composite coatings under water lubrication is described synthetically.